FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN DEPOSITO MUDHARABAH 1 BULAN DI BANK SYARIAH MANDIRI - Nurina Kusuma Lestari; Trikunawangsih (Media Ekonomi, 2014)
This Study aimed to examine the effect of interest rates, the level of profit sharing mudaraba deposits and inflation. Data taken from statistical reports at Bank Indonesia and Bank Syariah Mandiri from January 2009 to December 2013. This method used is the method of multiple linear regression. Using this method along with the underlying assumptions. The result showed that the rate of profit sharing mudaraba deposits and inflation positive influence on mudaraba deposits growth of Islamic banks, and interest rates negatively affect mudaraba deposits growth of Islamic banks.